PRO KONTRA EUTHANASIA DALAM KEHIDUPAN: MASALAH HUKUM, AGAMA, KEMANUSIAAN ERA MILLENIUM - Fauzi, Taty; Herlina, Nety (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
The problem of Euthanasia is a complex and highly controversial issue, so it involves many confusing questions that give rise to the pros and cons, some agree and reject the reason, violate nature as a human being who has no right to terminate ones life. The issue of life is the absolute property of the creator of nature and its contents. The oath of Hippocrates is a vow traditionally committed by doctors in which two ideas are present: the willingness to help the sufferer and refuse to help the person to commit suicide. These two ideas are included in the code of ethics of medicine. These oaths help medical workers to deal with new situations and problems because of the possibility of a